A Hybrid Pre-Treatment with Microwave and Hydrogen Peroxide for Performance Enhancement in Two-Stage Anaerobic Digestion - Ambrose, Herald Wilson (Curtin University, 2021)
A combined technology to enhance the anaerobic biodegradation of sewage sludge has been explored. The process involves a hybrid pre-treatment with microwave and hydrogen peroxide followed by, two-stage anaerobic digestion. The combined process resulted in enhanced anaerobic digestion performance in terms of biogas production, methane percentage, solid reduction and pathogen removal. Besides, the implications of hybrid treatment on sludge floc architecture and oxidative stress have also been reported.